2011
DOI: 10.1016/j.jacc.2011.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Flecainide Therapy Reduces Exercise-Induced Ventricular Arrhythmias in Patients With Catecholaminergic Polymorphic Ventricular Tachycardia

Abstract: Objective This study evaluated the efficacy and safety of flecainide in patients with catecholaminergic polymorphic ventricular tachycardia (CPVT) on top of conventional drug therapy. Background CPVT is an inherited arrhythmia syndrome caused by gene mutations that destabilize cardiac ryanodine receptor Ca2+ release channels. Sudden death is incompletely prevented by conventional drug therapy with β-blockers +/− Ca2+ channel blockers. The anti-arrhythmic agent flecainide directly targets the molecular defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
233
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 358 publications
(244 citation statements)
references
References 37 publications
8
233
0
3
Order By: Relevance
“…Since the first report by Watanabe et al, 18 the efficacy of flecainide in CPVT patients with RyR2 mutations has been reported. 19 In our study, 60% of the CPVT patients were on flecainide during the follow-up. Flecainide is reported to cause partial or complete suppression of high-risk VAs.…”
Section: Efficacy Of Flecainidementioning
confidence: 56%
“…Since the first report by Watanabe et al, 18 the efficacy of flecainide in CPVT patients with RyR2 mutations has been reported. 19 In our study, 60% of the CPVT patients were on flecainide during the follow-up. Flecainide is reported to cause partial or complete suppression of high-risk VAs.…”
Section: Efficacy Of Flecainidementioning
confidence: 56%
“…More recently, flecainide has emerged as an effective therapeutic agent for the treatment of CPVT both in combination with conventional β‐adrenoceptor blockade (van der Werf et al ., 2011; van der Werf et al ., 2012; Watanabe et al ., 2013) and as a monotherapy (Napolitano, 2016; Padfield et al ., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Beta-blokör tedavisi olguların büyük kısmında aritmi ataklarını önlemiştir (8) . Beta-blokör tedavisi altında semptomatik olan hastalarda flekainid başlanmalıdır (9) . Optimal medikal tedavi altında semptomların devam etmesi veya polimorfik VT atağı geçirmeleri durumunda ICD implantasyonu ve/veya sol kardiyak sempatik denervasyon önerilmektedir (10,11) .…”
Section: Discussionunclassified